FAKTOR – FAKTOR YANG MEMPENGARUHI PEMILIHAN MINAT KARIR MENJADI AKUNTAN PUBLIK PADA MAHASISWA JURUSAN AKUNTANSI - Alif Dio Setiawan; Rulyanti Susi Wardhani; Erwandy Erwandy (Jurnal Ilmiah Global Education, 2023)
Alif Dio Setiawan. 301 18 11 001. 2023. Factors Influencing the Selection of Career Interest in Becoming a Public Accountant for Students Majoring in Accounting (Study on College Accounting Students Batch 2018-2019 in Bangka Belitung). This study aims to determine the effect of financial rewards, professional training, work environment and labor market considerations on choosing a career interest to become a public accountant for students majoring in accounting class of 2018 and 2019 at state universities in Bangka Belitung. This research uses quantitative methods. The data used is primary data. Primary data was obtained from online interviews using the Google form. The sampling method used in this study is the saturated sample method in which the total population becomes the total sample to be examined. The sample studied was 296 students majoring in accounting consisting of 2 campuses namely, Bangka Belitung University and IAIN SAS Bangka Belitung. The results of this study indicate that financial rewards, professional training, work environment and labor market considerations have a positive and significant influence on the interest to become a Public Accountant among accounting students at the Bangka Belitung Islands provincial university.